Managerial Ability Concept and Measurement Models in Accounting: A Systematic Literature Review - Ghasem Blue; Manuchehr Roosta (Iranian Journal of Accounting, Auditing & Finance)
This study aims to systematically review all studies on managerial ability in accounting and identify the gaps between them. The breadth and variety of recent studies highlight the significance of this literature review. We identified 110 relevant studies published from 1990 to 2022 through multiple international scientific search engines, which we reviewed and categorized into ten thematic classes: performance, capital market, reporting quality, audit, investment, dividend policy and cash management, tax, corporate social responsibility, COVID-19, and miscellaneous. Our review shows that a considerable number of studies (43 out of 110) have focused on the relationship between firm performance, capital markets, and managerial ability due to the complex results in this field and various market perceptions of high-ability managers. However, few studies have explored the link between managerial ability, going concern, conservatism, and family firms. Moreover, most studies use Demerjian et al.'s (2012) model to measure managerial ability, which is an indirect method. Finally, we provide possible areas for improvement in the Demerjian et al. (2012) model and identify research gaps for future studies.